Low dispersal and ploidy differences in a grass maintain photosynthetic diversity despite gene flow and habitat overlap. Issue 9 (19th March 2021) - Olofsson, Jill K.; Curran, Emma V.; Nyirenda, Florence; Bianconi, Matheus E.; Dunning, Luke T.; Milenkovic, Vanja; Sotelo, Graciela; Hidalgo, Oriane; Powell, Robyn F.; Lundgren, Marjorie R.; Leitch, Ilia J.; Nosil, Patrik; et al.
Abstract: Geographical isolation facilitates the emergence of distinct phenotypes within a single species, but reproductive barriers or selection are needed to maintain the polymorphism after secondary contact. Here, we explore the processes that maintain intraspecific variation of C4 photosynthesis, a complex trait that results from the combined action of multiple genes. The grass Alloteropsis semialata includes C4 and non‐C4 populations, which have coexisted as a polyploid series for more than 1 million years in the miombo woodlands of Africa. Using population genomics, we show that there is genome‐wide divergence for the photosynthetic types, but the current geographical distribution does not reflect a simple habitat displacement scenario as the genetic clusters overlap, being occasionally mixed within a given habitat. Despite evidence of recurrent introgression between non‐C4 and C4 groups, in both diploids and polyploids, the distinct genetic lineages retain their identity, potentially because of selection against hybrids. Coupled with strong isolation by distance within each genetic group, this selection created a geographical mosaic of photosynthetic types. Diploid C4 and non‐C4 types never grew together, and the C4 type from mixed populations constantly belonged to the hexaploid lineage. By limiting reproductive interactions between photosynthetic types, the ploidy difference probably allows their co‐occurrence, reinforcing the functional diversity within this species. Together, these factors enabled the persistence of divergent physiological traits of ecological importance within a single species despite gene flow and habitat overlap.